Induction processes for job entrants in car service in France and Germany - Geiben, Marthe [Verfasser] (My University, 2015)
"Induction in enterprises is a crucial phase for each employee not only to become able to fulfil all relevant tasks but also to enable professional development as well as social and value-oriented integration into the new organisation. This is even more relevant for young people coming from initial vocational education and training with intermediate-level qualifications (European Qualification Framework 3 and 4). The research question of the presented doctoral thesis is to discover how induction processes are organised for these employees in two selected countries, and to interpret possible differences. Therefore, the author presents a mixed-method approach that focuses on qualitative case studies in selected enterprises in car service in France and Germany. This approach is complemented by an in-depth literature review of pedagogical literature and from other selected disciplines, for example Human Resources Development. This paper presents the conception and first results of the case studies. The focus therefore is on the description of induction processes. The few existing differences are interpreted by two aspects: Hofstede's cultural dimensions and organisational differences between the cases." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 1.2.4.2.1 Handel, Instandhaltung, Reparatur von Kfz und Gebrauchsgütern; T 3 Forschungsmethoden; T 1.5 International vergleichende Berufsbildungsforschung; Berufseinmündung; Zweite Schwelle; Betrieb; Personalgewinnung; Einarbeitung; Mittlere Qualifikation; Berufsanfänger; Kraftfahrzeuggewerbe; Fallstudie; Internationaler Vergleich; Bundesrepublik Deutschland; Frankreich; Empirische Untersuchung